Unsupported inferences of high‐severity fire in historical dry forests of the western United States: response to Williams and Baker. Issue 7 (2nd December 2013) - Fulé, Peter Z.; Swetnam, Thomas W.; Brown, Peter M.; Falk, Donald A.; Peterson, David L.; Allen, Craig D.; Aplet, Gregory H.; Battaglia, Mike A.; Binkley, Dan; Farris, Calvin; Keane, Robert E.; Margolis, Ellis Q.; et al.
Abstract Reconstructions of dry western US forests in the late 19th century in Arizona, Colorado and Oregon based on General Land Office records were used by Williams & Baker (2012; Global Ecology and Biogeography, 21, 1042–1052; hereafter W&B) to infer past fire regimes with substantial moderate and high‐severity burning. The authors concluded that present‐day large, high‐severity fires are not distinguishable from historical patterns. We present evidence of important errors in their study. First, the use of tree size distributions to reconstruct past fire severity and extent is not supported by empirical age–size relationships nor by studies that directly quantified disturbance history in these forests. Second, the fire severity classification of W&B is qualitatively different from most modern classification schemes, and is based on different types of data, leading to an inappropriate comparison. Third, we note that while W&B asserted 'surprising' heterogeneity in their reconstructions of stand density and species composition, their data are not substantially different from many previous studies which reached very different conclusions about subsequent forest and fire behaviour changes. Contrary to the conclusions of W&B, the preponderance of scientific evidence indicates that conservation of dry forest ecosystems in the western United States and their ecological, social and economic value is not consistent with a present‐day disturbance regime of large, high‐severity fires, especially under changing climate.